2018
DOI: 10.1002/cjp2.102
|View full text |Cite
|
Sign up to set email alerts
|

Anaplastic lymphoma kinase (ALK) gene rearrangements in radiation‐related human papillary thyroid carcinoma after the Chernobyl accident

Abstract: Childhood radiation exposure has been associated with increased papillary thyroid carcinoma (PTC) risk. The role of anaplastic lymphoma kinase (ALK) gene rearrangements in radiation‐related PTC remains unclear, but STRN‐ALK fusions have recently been detected in PTCs from radiation exposed persons after Chernobyl using targeted next‐generation sequencing and RNA‐seq. We investigated ALK and RET gene rearrangements as well as known driver point mutations in PTC tumours from 77 radiation‐exposed patients (mean a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 32 publications
1
11
0
Order By: Relevance
“…The average age of patients in our series was comparable to that of patients with PTCs unselected for genetic alterations: 43.4 (8-76) versus 46.8 (15-89) years, respectively (Cancer Genome Atlas Research Network 2014). The current study describes two pediatric patients, confirming previous observations of this fusion occurring in pediatric patients (Chou et al 2015, Vanden Borre et al 2017, Arndt et al 2018. The overall predilection for female patients appears to be more prominent in ALK-translocated group: 4.5:1 versus 2.7:1 among PTC patients unselected for ALK fusions (Cancer Genome Atlas Research Network 2014).…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…The average age of patients in our series was comparable to that of patients with PTCs unselected for genetic alterations: 43.4 (8-76) versus 46.8 (15-89) years, respectively (Cancer Genome Atlas Research Network 2014). The current study describes two pediatric patients, confirming previous observations of this fusion occurring in pediatric patients (Chou et al 2015, Vanden Borre et al 2017, Arndt et al 2018. The overall predilection for female patients appears to be more prominent in ALK-translocated group: 4.5:1 versus 2.7:1 among PTC patients unselected for ALK fusions (Cancer Genome Atlas Research Network 2014).…”
Section: Discussionsupporting
confidence: 87%
“…ALK-translocated thyroid carcinomas can occur both in patients with and without a history of radiation exposure. However, the prevalence of ALK fusions appears to be higher, up to 7.6-9% (Hamatani et al 2012, Arndt et al 2018, Efanov et al 2018, in PTCs from radiationexposed patients. An additional approach to increasing the chance of identifying ALK fusions is to exclude thyroid carcinomas with other, more common driver mutations such as BRAF, RAS, and RET/PTC.…”
Section: Discussionmentioning
confidence: 92%
“…Mutations of genes encoding the phosphoinositide-3-kinase–protein kinase B/ Akt -mammalian target of rapamycin (PI3K-PKB/ Akt-mTOR ) pathway were more frequent in ATC than PDTC (39% versus 11%). Anaplastic lymphoma kinase ( ALK ) gene rearrangements have been found in ATC [37] and in PTC [38]. GLIS3 rearrangements are prevalent in hyalinizing trabecular tumor (HTT), which is a rare TC with a characteristic trabecular growth pattern and hyalinization [39].…”
Section: Molecular and Genetic Factorsmentioning
confidence: 99%
“…A significant positive correlation between the 131 I thyroid dose and the incidence of chromosomal rearrangements was found, and the study reasonably claimed these could be induced by the radiation exposure. The dose-dependent incidence of the gene rearrangement was also reported for the ETV6-NTRK3 and STRN-ALK rearrangements [39,40]. By contrast, other reports concluded that the prevalence of the RET/PTC rearrangements were not associated with the exposure [72] or individual radiation doses [73].…”
Section: Radiation Signatures and Possible Mechanism Of Radiation mentioning
confidence: 94%
“…As a result, the RET/PTC fusion proteins are constitutively active, and stimulate the mitogen-activated protein kinase (MAPK) pathway and other signaling cascades in a ligand-independent way [34,35,36,37]. Other types of rearrangements, such as ETV6-NTRK3 [38,39] and STRN-ALK [40,41], were also identified in the Chernobyl childhood thyroid cancer (Table 1).…”
Section: Oncogenic Rearrangements In Childhood Thyroid Cancermentioning
confidence: 99%